Pengaruh Tingkat Pendidikan dan Mutasi Terhadap Kinerja Satuan Polisi Pamong Praja Kabupaten Belu Dengan Motivasi Kerja Sebagai Variabel Intervening - Herminus Bou; Philipus Tule; Agapitus H Kaluge; Stanis Man; Yulius Yasinto; Anggraeny Paridy (JURNAL MANAJEMEN PENDIDIKAN DAN ILMU SOSIAL, 2022)
Abstract: The purpose of writing this study is 1) An overview of education levels, transfers, work motivation, and ASN performance at the Belu Regency Satpolpp Office. 2) Level of education, mutation, and work motivation in influencing the performance of ASN at the Belu District Satpolpp Office. 3) The level of education and transfers in influencing ASN work motivation at the Belu District Satpolpp Office. 4) The level of education in influencing ASN performance at the Belu Regency Satpolpp Office through work motivation which is an intervening variable. 5) Movements affect ASN performance at the Belu Regency Satpolpp Office through work motivation which is an intervening variable. Furthermore, the research data was processed and analyzed using descriptive and inferential statistics. The results of the descriptive statistical analysis make it clear if the level of education, mutation, work motivation, and performance are in a good category. The results of the F test and t-test show if the level of education and transfers affect the performance of ASN Satpolpp Belu Regency. Then, work motivation without directly affecting the performance of ASN in the Belu Regency Satpolpp Office. The level of education has an indirect effect on performance through work motivation which is an intervening variable in the inferential statistical analysis which is not significant; including mutations do not have a significant impact on performance through work motivation which is the intervening variable. Abstrak: Penulisan kajian ini bermaksud guna: 1) Gambaran perihal tingkat pendidikan, mutasi, motivasi kerja maupun kinerja ASN pada Kantor Satpolpp Kabupaten Belu. 2) Tingkat pendidikan, mutasi, motivasi kerja dalam memengaruhi kinerja ASN di Kantor Satpolpp Kabupaten Belu. 3) Tingkat pendidikan dan mutasi dalam memengaruhi motivasi kerja ASN di Kantor Satpolpp Kabupaten Belu. 4) Tingkat pendidikan dalam memengaruhi kinerja ASN di Kantor Satpolpp Kabupaten Belu melalui motivasi kerja yang menjadi variabel intervening. 5) Mutasi memengaruhi kinerja ASN di Kantor Satpolpp Kabupaten Belu melalui motivasi kerja yang menjadi variabel intervening. Selanjutnya, data peneliti diolah dan analisis mempergunakan statistik deskiriptif maupun inferensial. Hasil analisis statistik deskriptif memperjelas bila tingkat pendidikan, mutasi, motivasi kerja, kinerja tergolong berkategori baik. Hasil uji F maupun uji t memoerlihatkan bila tingkat pendidikan dan mutasi memengaruhi kinerja ASN Kantor Satpolpp Kabupaten Belu. Kemudian, motivasi kerja tanpa memengaruhi secara langsung kepada kinerja ASN Kantor Satpolpp Kabupaten Belu. Tingkat pendidikan memengaruhi tidak langsung bagi kinerja melalui motivasi kerja yang menjadi variabel intervening dalam analisis statistik inferensial tidak signifikan; termasuk mutasi tidak memengaruhi bermakna bagi kinerja melalui motivasi kerja yang menjadi variabel intervening.